Wetlands in Brazil: classification, floristic composition and biological Nitrogen fixation (Research, Society and Development, 2022)
Wetland ecosystems represent about 20% of South America, and are classified according to the flood regime, which also influences on vegetation. Despite the value of ecosystem services provided by this environment, those areas are close to eradication in several parts of Brazil. These environments are extremely fragile. Flooded areas are subject to nitrogen losses (N) by leaching, becoming dependent on the N increases from biological nitrogen fixation (BNF). However, little is known about this process on wetlands. Understanding the adaptative strategies of these microorganisms and plants is essential for the maintenance and preservation of these ecosystems. The objective of this work is to present a literature review discussing aspects of floristic composition, biological nitrogen fixation, and morphophysiological adaptations that occur in the rhizobium-leguminous system in wetlands. For the bibliographic survey, articles and other academic works relevant to the topic were selected, in order to enrich the proposed discussion.